Association between bone turnover markers and the risk of imminent recurrent osteoporotic fracture. (2022) - ZHaNG, Bo; lI, lIKaNG; ZENG, HaoBIN; XU, XU; WaNG, rUotING; CHEN, MaoSHUI; GUoWEI, GUoWEI
No abstract available